Promovendo a alfabetização científica por meio da narrativa histórico-investigativa “Os diferentes ares obtidos da cal vermelha de mercúrio” - (:unkn) unknown (Universidade Federal do Amazonas, 2024)
Scientific and technological literacy (STL) aims to provide students with the skills to use their knowledge of scientific activities and scientific concepts in well-informed analyses and conscious decision-making. To this end, it is necessary to give opportunities to think about the nature of science (NOS), about the process of constructing science and establishing its credibility, about choices made by scientists, and other aspects. In this sense, several approaches emerge to corroborate this objective, among them is historical inquiry, which can use historical cases to simulate the investigative process experienced by scientists and, thus, provide such reflections. The historical inquiry narrative, with this purpose, follows a character (fictional or not) inserted in the context of the case and defines moments of pause to present questions that problematize the NOS and promote NOS inquiry; therefore students are engaged to reflect and discuss, being actively involved in the investigation process. The teacher's role is to read the material and mediate the time for questions to encourage students to reflect and express their ideas, involving them in the character's trajectory. Based on this, we sought to reflect on the potential of a historical-investigative narrative about the rupture with the phlogiston theory to promote scientific literacy; this being a crucial historical case in the establishment of Chemistry and, in a certain way, in the abandonment of knowledge more related to Alchemy and its principles. The NHI, called “The different airs obtained from red lime of mercury”, was developed considering this case, with the objective of providing opportunities for discussion and active investigation by students at the level of Higher Education through eleven questions/activities. The aspects of the nature of science explored in the historical inquiry narrative were identified and their contributions to promoting scientific literacy were highlighted. With this, it was possible to describe how different dimensions of science are involved in the historical inquiry narrative, such as the role of the socio-historical and cultural context, the role of access to resources and investment, the role of human interests and others in the production of scientific knowledge. Therefore, NHI is a resource that has the advantage of providing different in-depth analyses of the historical case, fostering the view of science as a human and historical construction. Such resources for working with the history of science are still in demand in the area, highlighting the importance of addressing this need and supporting a teaching and learning process that allows students to develop essential skills for their life in society.
Keywords: .; .; .; CIENCIAS HUMANAS: EDUCACAO; Alfabetização científica; Natureza da Ciência; Investigação histórica; História da Química